2010
DOI: 10.1007/s00421-010-1626-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pre-ejection period on post-exercise systolic blood pressure estimation using the pulse arrival time technique

Abstract: Pulse arrival time (PAT) is comprised of the vascular transit time (TT) through the arterial system and the pre-ejection period (PEP) in the heart. It has been used to predict arterial blood pressure (BP) without using a cuff. The aim of this study was to investigate the effects of including the PEP on the accuracy of cuffless systolic BP (SBP) estimation using the PAT technique in post-exercise recovery. Experiments were conducted on 22 normotensive participants. PAT, TT and PEP were determined from simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Since the PEP component depends on the electromechanical functioning of the heart, it can change independently of PTT and thus BP. For example, PEP changes in the same direction as PTT during exercise4 but in the opposite direction of PTT during vasoconstriction5. Note that several studies of PAT have demonstrated good correlation with BP by employing only exercise-induced BP changes1.…”
mentioning
confidence: 99%
“…Since the PEP component depends on the electromechanical functioning of the heart, it can change independently of PTT and thus BP. For example, PEP changes in the same direction as PTT during exercise4 but in the opposite direction of PTT during vasoconstriction5. Note that several studies of PAT have demonstrated good correlation with BP by employing only exercise-induced BP changes1.…”
mentioning
confidence: 99%
“…There is a significant difference in PTT baseline between the SB section and the PB section at 7 BPM (from 172.8 ± 20.1 to 176.8 ± 19.2 ms, p < 0.001). As PTT is inversely proportional to BP [10,41], the increase in the PTT baseline also suggests the beneficial effect of the SPB procedure to cardiovascular system. Figure 6 shows an illustration of the variations of PTT, SBP and DBP during the SPB procedure (from the same subject with Fig.…”
Section: Bp Was Lowered By the Spb Proceduresmentioning
confidence: 97%
“…The lack of statistical significance for the thickened CIMT hypertensive group may be because the abnormal stiffening and thickening affected this linear relationship. The research by Zhang and coworkers 32 reported that the inclusion of PEP in the upper-body PTT measurement could improve the accuracy of cuffless blood pressure estimation after exercise. This may indicate that including PEP in PTT could better reflect the change of vessel states.…”
Section: Discussionmentioning
confidence: 99%